2003
DOI: 10.1046/j.1365-2109.2003.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary cellulose level on specific dynamic action and ammonia excretion of the prawnMacrobrachium rosenbergii(De Man 1879)

Abstract: The feeding energetics of the prawn Macrobrachium rosenbergii (De Man 1879) were examined with respect to the effect of dietary fibre. Adult animals were fed semi‐purified diets with 0%, 5%, 10% and 15%α‐cellulose to determine the maximum aerobic scope that could be elicited by the increase in metabolism as specific dynamic action (SDA). The excretion rates of ammonia were also measured. Prawns fed all diets had significantly higher respiration rates after feeding due to SDA. Feed intake was not related to met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In addition, PmChi-2, similar to Pjchi-2, a molt-related chitinase isoform in M. japonicus, is highly expressed in gill especially during intermolt and down-regulated during post-molt. This fluctuating expression pattern during the molt cycle suggests PmChi-2 ′s direct role in molting [47], [48]. Thus, the repertoire of differentially regulated chitinase isoforms in gill and hepatopancreas are expected to be involved in chitin digestion for nutritional purpose, molting or other diversified roles of chitinase in M. rosenbergii.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PmChi-2, similar to Pjchi-2, a molt-related chitinase isoform in M. japonicus, is highly expressed in gill especially during intermolt and down-regulated during post-molt. This fluctuating expression pattern during the molt cycle suggests PmChi-2 ′s direct role in molting [47], [48]. Thus, the repertoire of differentially regulated chitinase isoforms in gill and hepatopancreas are expected to be involved in chitin digestion for nutritional purpose, molting or other diversified roles of chitinase in M. rosenbergii.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors may influence the use of the three different energy substrates (protein, carbohydrates, and lipids) by crustaceans, including diet (Pascual et al, 2004;Hayd et al, 2010;Rocha et al, 2013). In the diets of M. rosenbergii containing different levels of fibre, the O:N ratio varied from 10 (use of carbohydrates) to 49 (use of lipids) (González-Peña and Moreira, 2003). Chen and Nan (1994) observed that different species of marine shrimps fed the same commercial food used different energy substrates: Penaeus japonicus (Bate, 1888) and M. ensis (de Haan, 1844) used proteins, whereas P. monodon (Fabricius, 1798), P. penicillatus (Alcock, 1905), and P. chinensis (Osbeck, 1765) used lipids.…”
Section: Ingestion Rate and Defecationmentioning
confidence: 99%
“…Ammonia is the most common environmental pollutant in aquaculture systems; in fact, it is the main limiting factor in aquaculture practice [ 32 ]. Many studies have shown that ammonia is toxic to aquatic animals, including crustaceans, and it affects survival and the moulting process in decapod species [ 4 , 33 ]. Almost all previous studies reported that ammonia reduces survival in decapod species; however, its effects on moulting appear to be opposite in different species [ 8 , 9 , 34 ].…”
Section: Discussionmentioning
confidence: 99%